7th Non-Traditional Cement and Concrete - Bilek, Vlastimil (Trans Tech Publications, Ltd, 2024)
Selected peer-reviewed full text papers from the 7th International Conference ""Non-Traditional Cement and Concrete"" (NTCC2023) Selected peer-reviewed full text papers from the 7th International Conference ""Non-Traditional Cement and Concrete"" (NTCC2023), June 25-28, 2023, Brno, Czech Republic.
Keywords: elektronické knihy; electronic books